Amalan gratifikasi dalam kalangan masyarakat Islam di Aceh: Analisis dari perspektif hukum Islam / Fazzan - Fazzan, Fazzan (2017)
The practice of gratification has been common among Islamic society in Aceh. Despite the fact, this action is vaguely judged for its unclear status of wrong or right action to do due to many factors cause its existence; therefore, a comprehensive study related to gratification is needed. The practice of gratification has been common among Islamic society in Aceh, as if it has been an allowed deeds to do but maintained as a public secret. Despite the fact, this action is vaguely judged for its unclear status of wrong or right action to do due to many factors cause its existence; therefore, a comprehensive study related to gratification is needed. This study aims to explain the concept of gratification practised among Islamic society in Aceh vis-a-vis Islamic Law, to analyze the types of gratifications existed in Islamic society in Aceh and compared to Islamic Law, and to analyze the view of Islamic Law toward the gratification in Islamic society in Aceh. This study was assorted of field research and library research. The data used were primary and secondary data. The researcher used the descriptive-analytic in analyzing the data. The findings showed that the practice of gratification among the Islamic society in Aceh was done particularly as the service for the government employees, consisting of actions taking things at other’s disposal or taking other’s property in way of null and void (akl amwal al-nas bi al-batil). Generally, based on Islamic context the gratification practised in Islamic society in Aceh could be interpretated as an immoral act which was opposite to the concept of fairness (al-‘adalah), accountability (al-amanah), and responsibility. The types of gratification existed in Islamic society in Aceh were the gratification of tax abatement, the gratification of being the Civil Servant and Indonesian National Forces/Police (TNI/Polri), the gratification of effortlessness, traffic ticket, and release from prison. Those gratification practices among Islamic society in Aceh were substantially same as khiyanah (upon the country or the public service), al-ghashi (deception), al-ghasab (taking at other’s disposal), and al-rishwah (bribery) in which all those violations were stated in the nas. The gratifications practised among the Islamic society in Aceh were included in jarīmah al-ta‘zīr ‘alā al-ma‘asī (ta‘zīr for the immoral act) and al-ta‘zīr li maslahah al-‘ammah (ta‘zīr for the agitation). And the punishment for the offender of the law of gratification in Aceh follows the punishment for jarīmah ta‘zīr.